Penguatan Pengaturan Kebijakan Taman Nasional Berbasis Community Based Conservation Terhadap Hutan Adat di Indonesia - Syarif, Nawaz; Abdillah, Muhammad Torieq (Universitas Suryakancana, 2025)
AbstractEscalating deforestation and agrarian conflicts in and around national parks reveal the weak protection of customary forests and indigenous peoples’ rights despite constitutional recognition and Constitutional Court Decision No. 35/PUU-X/2012. This study is urgent because disharmony among sectoral regulations and a state-centric forest governance paradigm produce tenure insecurity and criminalization of indigenous communities. Using a normative legal research method with statutory and conceptual approaches, it analyzes the 1945 Constitution, Forestry Law, Conservation Law, Government Regulation No. 28/2011, Decision 35/PUU-X/2012, and literature on community-based conservation. The results show that integration of adat rights into national law remains partial and often reduced by licensing regimes, while CBC practices in Lore Lindu and Wakatobi National Parks demonstrate that tenure recognition and collaborative governance improve conservation effectiveness. The article concludes that a pluralistic, people-centered conservation policy grounded in adat law is required.AbstrakDeforestasi yang terus meningkat dan konflik agraria di kawasan taman nasional menunjukkan lemahnya perlindungan hutan adat dan hak masyarakat hukum adat meski telah ada pengakuan konstitusional dan Putusan MK 35/PUU-X/2012. Penulisan ini mendesak karena ketidakharmonisan regulasi sektoral dan paradigma pengelolaan hutan yang masih state-centric menimbulkan kerentanan tenurial dan kriminalisasi masyarakat adat. Penelitian menggunakan metode hukum normatif dengan pendekatan perundang-undangan dan konseptual terhadap UUD 1945, UU Kehutanan, UU Konservasi, PP 28/2011, Putusan MK 35/PUU-X/2012, serta literatur tentang community based conservation. Hasilnya menunjukkan integrasi hak adat dalam hukum nasional masih parsial dan sering tereduksi oleh rezim perizinan, sementara praktik CBC di Taman Nasional Lore Lindu dan Wakatobi membuktikan bahwa pengakuan hak tenurial dan tata kelola kolaboratif meningkatkan efektivitas konservasi. Disimpulkan perlunya reformulasi politik hukum konservasi yang pluralistik dan people-centered berbasis hukum adat.